Cinco ejes para pensar las humanidades digitales como proyecto de un nuevo humanismo digital. - Rodríguez-Ortega, Nuria (Università Oberta de Catalunya, 2018)
This text introduces the special issue of Artnodes magazine. Journal on Art, Science and Technology, dedicated to the digital humanities, under the subtitle "Policies, societies, knowledge", which brings together some of the most interesting contributions presented at the III Congress of the International Society of Hispanic Digital Humanities, as well as other contributions that have enriched and broadened the topics under discussion. In order to provide a better interpretation of the theoretical-methodological framework in which the articles that make up this special monograph make sense, a general delineation of the characteristics that define the field of the digital humanities is established. Finally, it indicates the five axes that, in the author's opinion, are key in the configuration of the digital humanities as a project for the construction of a new digital humanism.
Keywords: Humanidades digitales; Digital humanities; Postdigital society; Digital literacy; Data-centric paradigm; Hybrid ecologies